Analisi Brand Ambassador Vidi Aldiano dalam Meningkatkan Brand Awareness Produk ‘Somethinc’ di Watsons Surabaya - Angelin Gunardi (IPM2KPE, 2024)
This research aims to explore the influence of brand ambassador Vidi Aldiano on brand awareness of Somethinc products at Watsons Surabaya. Using a descriptive quantitative approach, this research involved 99 respondents who were Somethinc consumers at Watsons Surabaya. The analysis method used is multiple linear regression with the help of Statistical Product and Service Solution (SPSS). The research results show that brand ambassador Vidi Aldiano has a positive and significant influence on brand awareness of Somethinc products at Watsons Surabaya. Conclusions, discussed in the context of marketing strategies and promotion of local products in competitive markets. Keywords: Brand Ambassador, Brand Awareness